Reasons that take the user to urgent and emergency services in Lages-SC (Research, Society and Development, 2020)
Objective: to characterize the demand of users in urgent and emergency services in the city of Lages-SC. Methodology: A study of an applied nature, descriptive as to the objectives, quantitative quantification of the problem and transversal approach was carried out, without a period from September to October 2019, in an Emergency Department of Lages-SC. Questionnaire applied to users, addressing data on profile, responses, risk classification and reasons for choosing the service. Analysis performed using Microsoft Excel 2013. Results: survey of 80 patients, with prevalence of females and adult age group (35 years to 59 years). The main questions addressed about the respiratory system and the main reason for choosing the Emergency Care Unit (UPA) were identified as related to the urgency and emergency situation. 75% of the patients were classified as green by the nursing team, in disagreement with the reason for choosing the service. With this, it is evident the need for policies to raise public awareness about the levels of care, seeking to redirect and redistribute the flow to primary care.